2023
DOI: 10.1055/a-2005-7548
|View full text |Cite
|
Sign up to set email alerts
|

Comparing size measurement of colorectal polyps using a novel virtual scale endoscope, endoscopic ruler or forceps: A preclinical randomized trial

Abstract: Background and Aims: Accurate polyp size measurement is important for guideline conforming choice of polypectomy techniques and subsequent surveillance interval assignments. Some endoscopic tools (biopsy forceps [BF] or endoscopic rulers [ER]) exist to help with visual size estimation. A virtual scale endoscope (VSE) has been developed that allows superimposing a virtual measurement scale during live endoscopies. Our aim was to evaluate the performance of VSE when compared to ER and BF-based measurement. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Furthermore, we found that when using VSE, the percentage of size measurements that were within 25% of true size is more than doubled and significancy higher. The relative accuracies obtained for visual size estimation and VSE closely resemble those reported in preclinical trials obtained in simulated colon models 6–8. Similar to these preclinical studies, we found in our clinical pilot study that when using VSE the relative accuracy of polyp size measurement is increased from about 60%–70% (when using visual size estimation) to about 85% 6.…”
Section: Commentssupporting
confidence: 87%
“…Furthermore, we found that when using VSE, the percentage of size measurements that were within 25% of true size is more than doubled and significancy higher. The relative accuracies obtained for visual size estimation and VSE closely resemble those reported in preclinical trials obtained in simulated colon models 6–8. Similar to these preclinical studies, we found in our clinical pilot study that when using VSE the relative accuracy of polyp size measurement is increased from about 60%–70% (when using visual size estimation) to about 85% 6.…”
Section: Commentssupporting
confidence: 87%
“…A visual scale is then displayed on the screen. Endoscopists who used VSE achieved higher relative accuracy compared with visual estimation (85.4% vs. 66.8%; P <0.001) [25,26]. However, the virtual scale can only display on the right side of the laser, which potentially limits the usage scenario to measuring horizontally in the vertical plane.…”
Section: Discussionmentioning
confidence: 99%
“…This ruler is automatically deployed onto the mucosa with reference to the distance between the tip of the endoscope and the mucosal surface where the laser light is shed on. This ruler-based measurement outperformed biopsy forceps-based measurement in a recently published preclinical trial [5].…”
mentioning
confidence: 89%
“…The year 2023 has been a remarkable year for polyp size measurement, with the emergence of new technologies that can possibly help endoscopists estimate polyp size in a more accurate way than previously. These innovative technologies include both hardware-and software-based approaches [5,6].Recently, Fujifilm Corporation provided a laser-based measurement device on the market. With the use of a special endoscope integrated with a laser function (SCALE EYE; Fujifilm Corp., Tokyo), the endoscopy processor lays a ruler over the…”
mentioning
confidence: 99%